Project management for dummies - Portny, Stanley E. (Stanley Erwin) (Hoboken, N.J. : Wiley ; Chichester : John Wiley [distributor], 2013)
In today's business world, tight project deadlines and stringent expectations are the norm. This hands-on guide introduces you to the principles of project management and show you how to put them to use so you can successfully manage a project from start to finish.
Introduction -- Getting started with project management -- Planning time: determining when and how much -- Group work: putting your team together -- Steering the ship: managing your project to success -- Taking your project management to the next level -- The part of tens -- Appendix: Combining the techniques into smooth-flowing processes.
Previous ed.: 2010.
Includes index.
Keywords: Project management